2016
DOI: 10.1371/journal.pone.0165007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Domestic Goats as Models for Experimental and Natural Infection with the North American Isolate of Rickettsia slovaca

Abstract: Rickettsia slovaca is a tick-borne human pathogen that is associated with scalp eschars and neck lymphadenopathy known as tick-borne lymphadenopathy (TIBOLA) or Dermacentor-borne necrosis erythema and lymphadenopathy (DEBONEL). Originally, R. slovaca was described in Eastern Europe, but since recognition of its pathogenicity, human cases have been reported throughout Europe. European vertebrate reservoirs of R. slovaca remain unknown, but feral swine and domestic goats have been found infected or seropositive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The similarity of organ size between goats and humans makes these animals widely used. They are used in human medicine in research such as cardiac, orthopedic, model for infectious diseases or many others (Shiraishi et al 2012;Chen et al 2015;Zhang et al 2015;Lukovsky-Akhsanov et al 2016;Du et al 2018;Vandersteene et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of organ size between goats and humans makes these animals widely used. They are used in human medicine in research such as cardiac, orthopedic, model for infectious diseases or many others (Shiraishi et al 2012;Chen et al 2015;Zhang et al 2015;Lukovsky-Akhsanov et al 2016;Du et al 2018;Vandersteene et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rickettsial transmission to feeding ticks was also demonstrated, in the Americas, in opossums, lagomorphs, capybaras, small rodents ( R. rickettsii ) [ 40 – 44 ] and goats (North American isolate of R. slovaca ) [ 45 ]. In Europe, Heylen et al [ 46 ] showed that experimentally infected great tits ( Parus major ) transmit R. helvetica to feeding I. ricinus and facilitate co-feeding.…”
Section: Rickettsia Spp Infection In Animalsmentioning
confidence: 99%